Emerging challenges in meeting physiotherapy needs during COVID-19 through telerehabilitation - Joseph Ayotunde Aderonmu (Bulletin of Faculty of Physical Therapy, 2020)
Abstract Background Physiotherapy plays a significant role in rehabilitation. However, the emergence of the coronavirus disease 2019 (COVID-19) has posed a big challenge to its practice, especially regarding the level of contact with patients. There is a dire need for the exploration of rehabilitation options, other than in-person contacts, to limit the spread of the virus. This article explores telerehabilitation, its outcomes, and the challenges involved in the continuum of care of patients by physiotherapists in the face of the pandemic. Body Telerehabilitation is a vital tool which utilizes technology to link practitioners to patients. With its previous history of favorable outcomes for the rehabilitation of certain conditions, telerehabilitation has been widely recommended. However, issues exist on how well it can bridge the gap of physical touch in physiotherapy, its effectiveness in terms of outcomes and satisfaction across various conditions and large population sizes, and finally, its cost and effects, especially in developing countries. Conclusion Telerehabilitation is a necessary adaptation to ensure continued physiotherapy service delivery during the pandemic. However, more quality studies are recommended to evaluate its effectiveness and outcomes. Also, measures to ensure that developing countries are catered for in meeting the rising demands for physiotherapy services using telerehabilitation should be carried out.